Antioxidant capacity, phytochemical profiles, and phenolic metabolomics of selected edible seeds and their sprouts - Liu, Hong-Yan; Liu, Yi; Li, Ming-Yue; Ge, Ying-Ying; Geng, Fang; He, Xiao-Qin; Xia, Yu; Guo, Bo-Li; Gan, Ren-You (Frontiers in Nutrition, 2022)
Sprouts are recognized as nutritional and functional vegetables. In this study, 17 selected seeds were germinated simultaneously. The antioxidant capacity and total phenolic content (TPC) were determined for seeds and sprouts of all species. Both seed and sprout of white radish, with the highest antioxidant capacity, and TPC among all the 17 species, were further determined for phenolic metabolomics. Four phenolic classes with 316 phenolic metabolites were identified. 198 significantly different metabolites with 146 up-regulated and 52 down-regulated were confirmed, and high amounts of phenolic acids and flavonoids were found to be accumulated in the sprout. Several metabolism and biosynthesis, including phenylpropanoid, favone and flavonol, phenylalanine, and various secondary metabolites, were significantly activated. Significant correlations were found among FRAP, DPPH, ABTS, TPC, and phenolic profiles. Therefore, white radish sprout could be served as antioxidant and could be a good source of dietary polyphenols.